KNOWLEDGE LEVEL OF FRUIT-VEGETABLE AND CONSUMPTION DURING PANDEMIC COVID-19 AND ITS IMPACT ON CONSTIPATION AMONG TEENAGERS IN SMAN 1 DEPOK - Trina Astuti; Angie Rachel Hana; Wilda Kemalawati Fikroh (GIZI INDONESIA, 2022)
Fruit and vegetable (FV) consumption among teenagers in Indonesia is still relatively low. Based on Indonesia Basic Health Survey in 2018, 96.4 percent of teenagers have a low intake of FV and this can increase the risk of constipation. The purpose of this study was to assess the level of knowledge and FV consumption pattern and the impact on constipation at SMAN 1 Depok. The research design was cross-sectional with 206 high school students as subjects taken by proportional random sampling. Data was collected through an online questionnaire and tested statistically with Chi-square and Fisher-exact tests. The proportion of teenagers with a good level of knowledge is only 8.3 percent, while the others are moderate (55.8%) and not-good (35.9%). The average amount of FV consumption was 132.4±96.5 grams/day and 95.1 percent consumed less than the recommended amount. The average fiber intake was 6±2.5 grams/day, lower than the recommendation. It was found that 29.6 percent of teenagers were constipated. There was a significant relationship between FV consumption and FV accessibility (p=0,016), as well as constipation with gender (p=0,021) and fluid intake (p=0,027). Almost all teenagers have low consumption of FV and fiber intake and gender were found to be the dominant factor in constipation. It is recommended for the school to carry out continuous socialization for the students and parents about balanced nutrition, especially the importance of consuming 3 – 5 servings of FV a day